INSOLVENCY OF MICRO, SMALL AND MEDIUM ENTERPRISES IN THE REPUBLIC OF SERBIA - Đurić, Đuro; Jovanović, Vladimir (ACADEMIC REVIEW, 2024)
Micro, small and medium enterprises (MSMEs) are the most numerous in the Republic of Serbia, as well as in the European Union. In their business activities, they are faced with both economic and national legislation challenges. After the crisis caused by the COVID 19 pandemic, a new one caused by the war conflicts in Ukraine followed. MSMEs were particularly affected by the consequences of the crisis, through the rise in energy prices, and then a wide range of products and services. In Serbia they represent the backbone of the economy and development. However, the legal framework for solving business crisis is not adapted to their needs, but rather to the standards of large companies. Recent strategic documents in the EU and the world emphasize the need to introduce a special legal approach to MSMEs. Those instruments refer both to the prevention of insolvency, and to the insolvency procedure and liquidation of MSMEs. The aim of this paper is to point out the need for a different legislative approach to MSMEs in the Republic of Serbia. Using the normative method, the authors start from the legislation in power in Serbia and the EU, and by applying the statistical method, they analyze the current state of MSMEs in Serbia, and by applying the comparative legal method, they consider possible improvements in legislative solutions. In addition, by using a case study, an insight is given into the results that a special approach to the insolvency of MSMEs gives in practice.